2012
DOI: 10.7205/milmed-d-12-00121
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Reintegration of National Guard Veterans and Their Partners Using a Self-Directed Program of Integrative Therapies: A Pilot Study

Abstract: This article reports pilot data from phase I of a project to develop and evaluate a self-directed program of integrative therapies for National Guard personnel and significant relationship partners to support reintegration and resilience after return from Iraq or Afghanistan. Data are reported on 43 dyads. Intervention was an integrated multimedia package of guided meditative, contemplative, and relaxation exercises (CD) and instruction in simple massage techniques (DVD) to promote stress reduction and interpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 40 publications
1
49
0
Order By: Relevance
“…The seven single-group studies were not included in the metaanalysis; six of these studies resulted in a significant decrease in overall PTSD symptomatology (Collinge et al, 2012;Gordon et al, 2016;McCarthy et al, 2017;Price et al, 2017;Staples et al, 2013;Walker & Pacik, 2017), and the seventh study only showed a significant decrease in hyperarousal symptoms (Staples et al, 2013). For the 15 studies included in the metaanalysis, a random effects model effect size was calculated for all analyses because of the large heterogeneity in the interventions across the included studies (see Table S1).…”
Section: Results Of Individual Studies and Synthesis Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The seven single-group studies were not included in the metaanalysis; six of these studies resulted in a significant decrease in overall PTSD symptomatology (Collinge et al, 2012;Gordon et al, 2016;McCarthy et al, 2017;Price et al, 2017;Staples et al, 2013;Walker & Pacik, 2017), and the seventh study only showed a significant decrease in hyperarousal symptoms (Staples et al, 2013). For the 15 studies included in the metaanalysis, a random effects model effect size was calculated for all analyses because of the large heterogeneity in the interventions across the included studies (see Table S1).…”
Section: Results Of Individual Studies and Synthesis Of Resultsmentioning
confidence: 99%
“…The control conditions were waitlist (Carter et al, Rosenbaum, Sherrington, & Tiedemann, 2014). One study compared a massage condition to massage and body-oriented therapy (Price, 2005), and seven studies were single-group studies without a control condition (Collinge, Kahn, & Soltysik, 2012;Gordon, Staples, He, & Atti, 2016;Manger & Motta, 2005;McCarthy et al, 2017;Price et al, 2017;Staples et al, 2013;Walker & Pacik, 2017). Outcome measures were self-report measures for PTSD symptomatology as well as PTSD measures collected during clinical interviews; one study used a clinician-administered measure of complex traumatic stress (Kaiser et al, 2010).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…It also includes symptoms and treatments of PTSD as theoretical aspects, and intended services and expected outcomes linked to the PSD as emergent results [36][37][38]. From the stakeholders' perspective, there are four roles and tasks of PSD (detection and intervention when the veteran is anxious, contributing to a feeling of safety, a sense of relaxation and socialisation), two major undesirable events that can occur with the service dog (public access and stigmatization), nine potential effects of the PSD, three potential organizational impacts of the service dog and 12 co-factors affecting accessibility and efficacy of the intervention with PSD.…”
Section: Resultsmentioning
confidence: 99%
“…Couple-based programs and interventions have been shown to be effective in increasing marital satisfaction (Lewis et al, 2016; Monson et al, 2004) and in reducing adverse outcomes, such as intimate partner violence (Taft et al, 2015; Taft et al, 2013). Programs like Mission Reconnect- a partner-based, self-directed program of integrative therapies, including massage, have demonstrated significant improvements in PTSD, depression and stress (Collinge, Kahn, & Soltysik, 2012). However, further work is needed in this area to determine if increases in marital satisfaction as a result of couple-based therapies contribute to further improvements in mental health outcomes in the long-term, after interventions have ended.…”
Section: Discussionmentioning
confidence: 99%